Transport fuels from Australia's gas resources - Clark, Robert; Thomson, Mark (New South Publishing, 2014)
The transport sector in Australia depends heavily on imported oil-based fuels. With this comes the ever-present risk of oil supply shortages. But Australia is gas-rich and oil-poor, so it makes practical sense to assess how our own gas resources can be used to produce these fuels. Natural gas can be used directly as a fuel, blended with diesel in modified diesel engines, and converted into a conventional liquid fuel - all at a modest cost. This book, written by Australia's leading experts in the field, demonstrates how using natural gas as a transport fuel could increase our fuel self-sufficie.